Formation of students' knowledge by teaching the epic "Kutty Bilik" by J. Balasagun - Айтенова, Динара; Ченгел, Хулия Касапоглу; Мынбаева, Акбилек; Халикова, Нурила; Байтенова, Айгуль (Pedagogy and Psychology, 2023)
This research article examines the ways of formation and development of students' thinking abilities through teaching the works of famous personalities of the Karakhan era. The methods and techniques aimed at discussion, development of thoughts, wise thoughts in sagas related to the activation of creativity of the individual in the era of Karakhan are shown. The teaching of the discipline is based on the mysterious plot of the great work of medieval Turkic culture, now included in the golden fund of world literature-"Kutty Vali" by Zhusup Balasagun, including the characteristic features of the teaching methodology of sagas, designed to show with the help of logical reasoning that the consciousness, customs and traditions of the peoples who lived on the Kazakh land ten centuries ago, so the same vividly hints at the genesis and features, too. Thanks to reading the saga of Zhusup Balasagun "Kutty bilik", students are growing interest in spiritual value, fiction. From the saga, which continues to amaze and amaze with its elementary wisdom, students understand the origin of the people, their art, culture and literature, history and philosophy. When it comes to considering these important issues, it is necessary that all conditions for the improvement and development of their creative abilities be created through the teaching of the epic saga.